A review and reframing of participatory urban dashboards. (March 2020) - Lock, Oliver; Bednarz, Tomasz; Leao, Simone Z.; Pettit, Christopher
Abstract: Urban dashboards form part of a wider ecosystem of urban data platforms and products being created and used in an age of ever-increasing digitalisation of city services and governance. The design of these dashboards typically consolidates information into a single view for government and industry to efficiently and effectively monitor the performance of urban systems – such as those of energy, built form, transport, culture, performance, innovation and health. Many of these dashboards focus on a one-way flow of data and thus do not cater specifically to the functions of public participation, community engagement and collaboration. With growing concerns in digital democracy, there is an increasing demand for software and tools that maximise human-centred design elements and include such participatory and collaborative features. The current trajectory of their development can be reframed to support this. This review frames a more porous definition of the term, integrating the concept of the urban dashboard among other existing digital urban planning methods and tools. It highlights the potential for further work to integrate with emerging media such as virtual, augmented and mixed realities. Reflecting on a diverse range of literature, the result of this paper is a classification system and key recommendations for development and understanding participatory urban dashboards as they fall within the existing lexicon of Smart City platforms and technologies. Highlights: Urban dashboards are urban governance technologies used to understand, monitor, analyse the performance of cities There exists of paucity of these which support the multi-way flow of information between key actors in city planning. A classification system was developed, identifying physical and digital features which can enable a more participatory approach. Key recommendations can be made to form a more porous definition of 'participatory urban dashboards'. Advantages of emerging interfaces through Mixed Reality are discussed, supporting this.